Relative humidity measurement sensor based on polyvinyl alcohol coated tilted fiber Bragg grating. (12th October 2021) - Saini, P K; Prakash, O; Kumar, J; Purbia, G S; Mukherjee, C; Dixit, S K; Nakhe, S V
Abstract: This paper presents the development and studies of a relative humidity (RH) sensor based on polyvinyl alcohol (PVA) coated tilted fiber Bragg grating (TFBG). The TFBG used was inscribed in-house using 255 nm UV radiation generated from frequency doubled copper vapor laser. The cladding portion of the TFBG region was partially etched with 40% hydrogen fluoride acid. Partially cladding etched TFBG was coated with thin layer of PVA using dip-coating technique. PVA among the class of humidity sensing materials enables the strong coupling of cladding modes of TFBG with surrounding medium humidity level. The transmission losses of cladding modes of PVA coated etched TFBG changes as the humidity level of surrounding environment changes. The developed sensor was studied for RH ranging from 45% to 95%. The average sensitivity obtained in the investigated RH range is 0.095 dB/%RH. The sensor shows good linearity in the two ranges 45%–75% and 75%–95% of RH. The obtained sensitivity was 0.045 dB/%RH in the range 45%–75% and 0.144 dB/%RH in the range 75%–95%. Maximum sensitivity obtained from the experimental result was 0.297 dB/%RH.